The effect of extract andropogon zizanioides urban roots as a repelent to Aedes Aegypti mosquito - Mahardika Agus Wijayanti, Mahardika Agus Wijayanti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Dengue haemorrhagic fever (DHF) is one of the viral infections transmitted by mosquitoes that still remains a health problem in Indonesia. Attempts to overcome this disease through experimental studies, in order to get rapid and right diagnosis, specific treatment and vaccine development have not been satisfactory. The main vector of DHF are Aedes aegypti and Aedes albopictus mosquito. Self protection againts mosquito bites could be done by using repelent. Lorosetu (Andropogon zizanioides urban) is a plant belonging to one family of fragrant grass, usually used as a soap fragrance or supplementary medication. Its root is commonly used to chase insect In the wardrobe. The aim of this study was to Investigate the effect of A. zizanioides Urban extract as a repelent to A. aegypti mosquito in the laboratory. In this study, time series observation using various concentration of extract A. zizanioides Urban as a repelent to A. aegypti was done. The result analized by Spit-plot and T-test showed that 25% extract of A. zizanioides Urban roots has the effect as a repelent within one hour, while the 50% and 100% concentration have the effect within two hours.Key words: Dengue Haemorrhagic Fever - Aedes aegypti - root extract - Andropogon zizanioides Urban root - repellent